Advancing the strategic impact of human-centred design - van der Bijl-Brouwer, Mieke; Dorst, Kees (Design studies, 2017)
Many organisations realise that becoming more human-centred is key to dealing with today's innovation challenges. Human-centred design (HCD) has potential to contribute to this goal. However, its current impact on strategic innovation is limited. In this paper we describe the evolution of HCD methods to date, and the challenges and opportunities of applying HCD in strategic innovation. We show that these challenges could be addressed by augmenting HCD with methods from the field of design innovation. To do this, we propose the NADI-model that links these two worlds by considering the different layers of practices and knowledge they contain, and show how the deepest level of this model can bridge human-centred design and strategic innovation. •Human-centred design has potential to contribute to strategic innovation.•Different human-centred design methods generate different layers of knowledge.•The layers of needs and aspirations (NADI) are solutions, scenarios, goals and themes.•Strategic impact requires design methods informed by themes.•Themes bridge the fields of human-centred design and design innovation.